Chemical Formulation : An Overview of Surfactant-based preparations used in Everyday life - Hargreaves, Tony (The Royal Society of Chemistry, 2003)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. Chemical formulation can be traced back to Stone Age times, when hunter-gatherers attached flint arrowheads to shafts using a resin made from birch bark and beeswax. Today, formulated preparations are part of everyday life. Formulations based on surfactants are by far the most prolific, from shampoos and shower gels to emulsion paint and polishes. This book discusses the chemical technology of surfactants and related chemicals, using over forty examples of everyday products. Some basic theory on surface chemistry, molecular interactions and surfactant function is included to aid understanding. Chemical Formulation: An Overview of Surfactant-based Preparations Used in Everyday Life then goes on to look at wider aspects such as surfactant manufacture, raw materials, environment, sustainability, analysis and testing. Throughout, common chemical names are used for formulation chemicals, further aiding the readability of the book. Bridging the gap between theory and application, this book will be invaluable to anyone wishing to broaden their knowledge of applied chemistry, including students on A level, BTEC and technician courses. It will also be of benefit to those new to the formulation industry